Exploring adventure tourism trends through image content analysis of Instagram posts - Stanišić, Tanja; Lazarević, Sonja; Kopeva, Diana (Hotel and Tourism Management, 2024)
Purpose – The main objective of the paper is to contribute to testing the usefulness of image content analysis in the assessment of trends in the tourism market, as well as to draw conclusions about contemporary tendencies in the adventure tourism market. Methodology – The image content analysis is a key methodological tool in this research, supported by comparative and cluster analysis. A detailed analysis of trends in adventure tourism is carried out through the assessment of geographical and temporal characteristics, types of adventure activities and user representation by gender. Findings – The results of the research indicated the significant role of developing countries as adventure tourism destinations, the absence of seasonality, the dominance of soft adventure activities and women as participants in this type of tourism. In addition, the research made it possible to identify certain new activities and conclude on the diversification of the offer, as well as the classification of activities according to the gender structure of the participants. Implications – The results can be useful to the creators of the offer on the adventure tourism market, but also to the tourists themselves in terms of ideas and motivation. In a theoretical sense, the paper should contribute to highlighting the prevailing views in the literature on the key features of adventure tourism.